How Indonesian Women Micro and Small Entrepreneurs Can Survive in Covid-19 Pandemic? - Nugroho, Lucky; Badawi, Ahmad; Hidayah, Nurul (LP2M INSURI Ponorogo, 2022)
This article aims to analyze the conditions and success tips of micro and small women entrepreneurs during the covid-19 pandemic. This article is the output of community service lecturers at Mercu Buana University. The method used is socialization for micro and small women entrepreneurs assisted by the North Meruya Village, West Jakarta, Indonesia. Moreover, the article method uses descriptive data supported by primary data collected from eight micro and small women entrepreneurs who participated in the socialization. The result of this socialization activity is that it is known that the sales turnover of micro and small entrepreneurs during the COVID-19 pandemic has decreased significantly. However, there are tips for micro, and small women entrepreneurs who can survive and increase their sales turnover through e-commerce in promoting, marketing, and selling their products and services. This study implies that micro and small women entrepreneurs need to innovate in running their businesses and maintain their sales turnover by switching to the business transaction process supported by digital applications.